1981
DOI: 10.1507/endocrj1954.28.51
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin stimulates gluconeogenesis in fasted rats.

Abstract: The effect of calcitonin (CT) on gluconeogenesis was studied in fasted rats. The subcutaneous administration of CT (80 MRC mU/100 g BW) produced a significant increase in serum glucose concentration and a corresponding decrease in serum lactic acid, free fatty acid and alanine concentrations. These alterations were dose-dependent (20 and 40 MRC mU/100g BW). On the other hand, the serum glucose concentration was significantly elevated by a single intraperitoneal injection of alamine (100 mg/100 g BW). This incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…The Pck2 and G6pc3 data also partially support this indication (Figure S5B, C). This finding is, of course, not entirely surprising since CT alone can induce hepatic gluconeogenesis [45][47]. The important point to be made here is that neither agent alone is the magic bullet.…”
Section: Discussionmentioning
confidence: 69%
“…The Pck2 and G6pc3 data also partially support this indication (Figure S5B, C). This finding is, of course, not entirely surprising since CT alone can induce hepatic gluconeogenesis [45][47]. The important point to be made here is that neither agent alone is the magic bullet.…”
Section: Discussionmentioning
confidence: 69%
“…The results of our previous investigations allow consider that it is mediated both due to the inhibitory effect of CT on insulin secretion [11,12], the decreasing of glucose consumption by peripheral tissues [13] and due to the intensification of glycogenolysis process [14,15]. These changes result in hyperglycemia, insulin resistance, and impaired glucose tolerance.…”
Section: Methodsmentioning
confidence: 95%
“…Recently it has been reported that CT stimulates gluconeogenesis from alanine, lactate and pyruvate in fasted rats (Yamaguchi 1981b), and from alanine and glutamine in isolated rat hepatocytes (Yamaguchi and Williamson 1983). However, the mechanism of CT actions remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…This effect of CT is not dependent on the release of epinephrine from the adrenal glands (Yamaguchi 1980) or glucagon from the pancreas of rats (Yamaguchi 1981a). More recently it has been shown that CT stimulates glucose production from alanine in the liver of rats (Yamaguchi 1981b) and in isolated rat hepatocytes (Yamaguchi and Williamson 1982).…”
Section: Introductionmentioning
confidence: 90%